Euro Area Policies : Staff Report. (IMF Staff Country Reports; Country Report, 2005)
This paper focuses on euro area policies. The monetary policy stance remains appropriate for now. Fiscal policies are falling well short of consolidation requirements, and the area remains insufficiently prepared for the looming demographic shock. Past fiscal policy failures, notably insufficient adjustment during economic upswings, have strained the Stability and Growth Pact (SGP) and EMU's fiscal framework. IMF staff has welcomed certain elements of flexibility in the SGP reforms while regretting the vagueness and open-endedness of others. Center-led structural reform programs have struggled to deliver.